Proposed enrichment activities for developing leadership skills through girl scouting - Pada, Loreto Somera 1930-; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1977)
This paper is directed at vitalizing the present Junior Girl Scouting Program by suggesting activities for developing leadership skills particularly among gifted girl scouts. The suggested enrichment activities and strategies were derived from scouting pamphlets, brochures and manuals, and literature found in books, journals and research papers. The core of this paper was grouped into two namely: enrichment activities in scouting, and strategies and techniques to develop leadership skills.
"October, 1977."
Vita.
Thesis (Master of Arts in Teaching Special Education - Giftedness)--University of the Philippines, Diliman
Keywords: Leadership -- Study and teaching (Elementary) -- Activity programs -- Philippines; Girl scouts -- Philippines; Scouting (Youth activity) -- Philippines